A Model of Conservation, Promotion and Development of Cultural Heritage Values Through Folk Ways of Life of People in the Northeast - Suvannasri, Surapan; Armartmultree, Iam (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of this research paper are 1) to collect types and forms of indigenous phagnum, 2) to study cultural heritage values ​​of indigenous peoples, 3) to present a model for conservation, promotion and development of cultural heritage values ​​of indigenous peoples. The samples used in this research were 276 monks and 468 lay monks by simple random sampling and size determination using Krejcie & Morgan tables. folk medicine for the layperson has chosen a group of elders, village sages writers group local media group a group of politicians or local leaders Educational scholars, Mo Lam groups, experts data analysis After obtaining information from observations and in-depth interviews, All data were selected, categorized, interpreted, and analyzed to propose values ​​of indigenous cultural heritage. Then bring to synthesize the results of factors affecting the conservation, promotion and development of indigenous plants. and guidelines for conservation, promotion and development of indigenous species Then present the results by descriptive analysis according to the issues. The results of the research showed that: 1. Types of folk remedies divided by structural characteristics Content And how to present the content, consisting of 1) Phayana proverbs 2) Phayasak blessing and 3) Phawaowai The form of Phaya can be divided into 3 forms which are 1) Language, 2) Poetics and 3) Content. 2. The value of folk wisdom to the way of life of the people in the Northeast consists of 2 areas which are 1) self-development such as beliefs, education, gratitude and occupation and 2) social development such as Family, Economy, Politics and Government. 3. Conservation, promotion and development of folk cultural heritage values ​​consist of 2 methods which are 1) Factors affecting the conservation, promotion and development of folk wisdom such as the Bolt Lam family and folk literature 2) Guidelines for conservation, promotion and development of folk customs Folk practices include: 1. Educational institutions should prepare a curriculum for students to learn as to bring folk into a true way of life. Should proceed at the same time in all 3 systems, namely the informal and informal system 2.Government organizations such as District culture and the Provincial Cultural Council Office of Buddhism, the Fine Arts Department, the Cultural Council of the educational institution or the person responsible for culture Must study, research and survey data from palm leaves Internet system Bring new inspections to be modern and interesting. 3. Set up a community cultural learning center for youth and interested parties to learn and learn. By creating a standardized learning resource center Organize activities continuously and seriously. Organize continuous training for speakers with volunteer spirit from all sectors and creating a variety of folk learning materials.